Fundamental neutron physics beamline at the spallation neutron source at ORNL - Fomin, N.; Greene, G.L.; Allen, R.R.; Cianciolo, V.; Crawford, C.; Tito, T.M.; Huffman, P.R.; Iverson, E.B.; Mahurin, R.; Snow, W.M. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2015)
We describe the Fundamental Neutron Physics Beamline (FnPB) facility located at the Spallation Neutron Source at Oak Ridge National Laboratory. The FnPB was designed for the conduct of experiments that investigate scientific issues in nuclear physics, particle physics, astrophysics and cosmology using a pulsed slow neutron beam. We present a detailed description of the design philosophy, beamline components, and measured fluxes of the polychromatic and monochromatic beams.